Mixed-methods analysis of sickness behavior during a natural experiment: An integrative single-case study - Schubert, Christian; Seizer, Lennart; Sophia Lauby, Nina Camille; Fuchs, Dietmar (Comprehensive Psychoneuroendocrinology, 2025)
Sickness behavior is a coordinated set of psychological changes mediated by immune system activity, e.g., during infection and wounding. It is an adaptive response to conserve energy and resources in support of immune activity and to protect the community by signaling others that one is ill. In this integrative single-case study, a 27-year-old healthy woman collected her entire urine over a period of 63 days in continuous 12-h intervals (126 measurements in total). In addition, among other regular psychological assessments, she completed an emotional state questionnaire (EWL) each morning and evening, and had an in-depth psychological interview once a week. In the urine samples, neopterin, cortisol, and creatinine were measured. Coincidentally, the subject experienced a period of sickness during the study period, lasting two days (from 12-h interval 21 to 24), accompanied by fatigue, vomiting, diarrhea, low-grade fever, and increases in urinary neopterin and cortisol concentrations. During this sickness period, structural breaks occurred in the time-series of two positive emotional states, i.e., performance-related activity and general feeling of comfort, with significant drops in their mean levels lasting for over 50 days until the end of the study. The intensive longitudinal data set collected in this integrative single-case study makes it possible to adopt a biopsychosocial meta-perspective (bottom-up, top-down) when interpreting the results.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Biopsychosocial; Cortisol; Integrative single-case study; Neopterin; Psychoneuroimmunology; Sickness behavior; Time series